Essential Ecosystem Area Policies as a Means to Promote Participatory and Inclusive Conservation in Forest Landscape Governance: Centering Perspectives of Marginalized Women in Taman Kili-Kili, Indonesia - Hendrastiti, Titiek Kartika; Setiahadi, Rahmanta; Kusujiarti, Siti; Pratiwi, Dian; Safrudi, Hale Irfan (Forestry Faculty, Universitas Hasanuddin, 2024)
This study analyses dimensions of participatory forest landscape governance of the Essential Ecosystem Area (EEA) of Taman Kili-Kili, Indonesia. The voices of marginalized communities, and especially women, are rarely incorporated into forest landscape governance and conservation policies. The recently established Indonesian EEA policy mandates a participatory approach, with explicit requirements to involve marginalized groups and gendered perspectives. However, on a practical level, policy formulation and application unfold in very different ways. Using a Postcolonial Feminist Participatory Action Research (PFPAR) approach, we center local communities' power relations in our analysis as a specific means for drawing out various intersectional relations to conservation areas. The study found that local communities around EEA Taman Kili-Kili have a clear interest in participating in inclusive mangrove forest management models as they not only have the knowledge and capacity, outcomes significantly affect their lives and livelihoods. Findings suggest that the activism of local communities, specifically in the form of various women's gatherings, is reshaping policy milestones and opening up pathways towards gender and ecological justice.